Respuesta :
Answer:
Equation of the parabola is [tex]\left(y+3\right)^{2}=-24(x+4)[/tex]
Step-by-step explanation:
We have to find the equation of a parabola with vertex is (-4,-3) and a directrix x=2.
As vertex is (-4,-3) that means parabola is in third quadrant.
So the standard formula of the parabola will be y²= -4px through origin (0,0).
But when a parabola is shifted from origin to the left of y axis so the equation will be (y-shifting form y axis)² = -4(distance between vertex and directrix)(x-shifting from x axis)
[tex]\left\{y-(-3)\right\}^{2}=(-4\times 6)\left\{x-(-4)\right\}[/tex]
[tex]\left(y+3\right)^{2}=-24(x+4)[/tex].
Answer:
Standard form (y + 3)² = -24( x + 4).
Step-by-step explanation:
Given : parabola that has a vertex of (–4, –3) and a directrix of x = 2.
To find : Which is the standard form of the equation of the parabola.
Solution :We have given that vertex of (–4, –3) and a directrix of x = 2.
Standard form eqauation of parabola its axis of symmetry is parallel to the x-axis : (y-k)² = 4p(x-h).
Where, vertex = (h,k) , directrix is x = h - p.
h = -4 , k= -3;
Directrix : 2 = -4 -p
Then p = -6
Now, plugging the values of vertex and p in standard form.
(y - (-3))² = 4(-6)( x - (-4)).
(y + 3)² = -24( x + 4).
Therefore, Standard form (y + 3)² = -24( x + 4).